Case Report: Psychopathological Syndromes in the Course of Lupus Erythematosus and the Co-occurrence of Lupus Erythematous With Mental Disorders - Stelmach, Ewa; Masiak, Jolanta (Frontiers in Psychiatry, 2021)
Introduction. Systemic lupus erythematosus is an autoimmune disease that leads to a chronic inflammatory process in tissues and organs. The neuropsychiatric systemic lupus erythematosus (NPSLE) is a set of neuropsychiatric symptoms that derive from the central and peripheral nervous system and are observed in the course of SLE. Case report and final diagnostic and therapeutic results. A diagnostic and therapeutic process in a patient with the signs and symptoms of SLE and bipolar disorder (BD) has been described. BD has been diagnosed as a primary disorder while SLE as a comorbid disease. Discussion. Common immunological mechanisms in BD and SLE are the reason for difficulties in diagnosing BD with co-occurring SLE. It should be determined whether BD is a primary disorder or a secondary component of a clinical picture of SLE (NPSLE) or whether mood and/or psychotic disorders are the result of steroid therapy in the course of SLE (SIMPD). Conclusion and the patient’s perspective. The presented case report is a unique description of a patient with a primary diagnosis of BD with comorbid SLE.